The Impact of Neurofibromatosis Type 1 on the Health and Wellbeing of Australian Adults. Issue 6 (19th April 2015) - Crawford, Hilda A.; Barton, Belinda; Wilson, Meredith J.; Berman, Yemima; McKelvey‐Martin, Valerie J.; Morrison, Patrick J.; North, Kathryn N.
Abstract: The complications of neurofibromatosis type 1 (NF1) are widespread, unpredictable and variable and each person's experience of this disorder is unique. However, few studies have addressed the impact of NF1 from an individual's perspective. This qualitative study aims to identify the ways in which NF1 impacts upon affected Australian adults. Sixty adults with NF1, with a range of disease severity and visibility participated in a semi‐structured interview about the ways in which NF1 impacted upon their life and health. Data were analyzed using grounded theory methodology. Results indicated that NF1 impacts upon affected adults in five major ways: 1) cosmetic burden of disease 2) learning difficulties 3) concerns about the risk of passing NF1 to offspring 4) uncertain disease progression, and 5) pain. Participants identified the aspects of NF1 that bothered them the most, creating a hierarchy of NF1 concerns within the cohort. Importantly, mildly affected adults shared many of the same concerns as those more severely affected. This study enhances our current understanding of the impact of NF1 in adulthood, and augments existing recommendations for the care of these patients.